Numerical simulation of heat distribution in RGO-contacted perovskite solar cells using COMSOL - Zandi, Soma; Saxena, Prateek; Gorji, Nima E. (Elsevier, 2020)
A 3D simulation of optical photogenreation, electrical characteristics, and thermal/heat distribution across the structure of a perovskite solar cell with a reduced graphene oxide (RGO) contact is presented. COMSOL Multiphysics package has been used to solve the coupled optical-electrical-thermal modules for this hybrid cell where the RGO added as the bottom electrode instead of a conventional metallic contact to enhance the heat dissipation towards a higher device stability. The Wave Optic module, Semiconductor module, and Heat Transfer in Solid module were coupled and solved for the proper input parameter values taken from relevant literature. The optical photogeneration, current-voltage characteristics, electric-field and the thermal maps of the cell are presented. The RGO contact doesn’t significantly impact on the optical and electrical output of the cell, but it accelerates the heat dissipation. The heat is mainly generated across the cell from the light absorption, Shockley-Read-Hall non-radiative recombination, and Joule heating. Compared to the cell with the Au electrode, the RGO contacted cell is showing a minimized heat accumulation and gradient at the bottom junction of the RGO/Spiro interface which promises a thermal stability of the cell. The nan-radiative and joule heat distribution also show a moderated density for the RGO contacted cell which are assigned to the high heat conductivity of the RGO layer compared to traditional metallic electrodes. Our simulations results are of the rarely presented thermal simulations for such devices and prove the superiority of graphene over plane metallic contacts for heat dissipation and thermodynamic aspect of a solar cell.
Keywords: Perovskite; Graphene; RGO; Solar cells; COMSOL; Heat distribution; Simulation